Description of the Last Instar Larva of Platylestes platystylus (Rambur, 1842) from Kerala, India (Odonata: Lestidae) - Chandran, Ayikkara Vivek; Jose, Subin Kaniyamattathil; Dawn, Prosenjit (Zootaxa, 2023)
The description of the final instar larva and the subsequent exuvia of Platylestes platystylus (Rambur, 1842) is given based on a single male larva collected from Kerala and reared in the laboratory. A brief account of the habitat of the damselfly and an updated key to the larvae of genera of Family Lestidae Calvert, 1901 are also provided.